Implementation of IoT for Monitoring Ambient Air in Ubiquitous AAL Environments - Silva, Madalena P.; Gonçalves, Alexandre L.; Dantas, M. A. R.; Vanelli, Brunno; Manerichi, Guilherme; Santos, Stephan A. R. D. Dos; Ferrandim, Mauri; Pinto, A. R. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2015: Anais do V Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2015)
This paper investigates WSN (Wireless Sensor Networks) applications in health, and proposes implementation of IoT (Internet of Things) with ZigBee for Ambient Condition Monitoring in a Ubiquitous AAL (Ambient Assisted Living) environment. The data obtained from sensors (temperature and humidity) were combined so as to obtain the dew point temperature, which can be used as a thermal discomfort indicator of the users with some pre-disposition to respiratory problems. Monitored variables are transmitted via the Internet and stored in the supervisory system ScadaBR. These data can be monitored by the ScadaBR HMI (Human-Machine Interface) or consumed by another application so that caregivers can provide care to patients with a history of asthma attacks.